The Potential Relationship Between Serum Irisin Concentration with Inflammatory Cytokines, Oxidative Stress Biomarkers, Glycemic Indices and Lipid Profiles in Obese Patients with Type 2 Diabetes Mellitus: A Pilot Study - Khajebishak, Yaser; Faghfouri, Amir Hossein; Soleimani, Ali; Peyrovi, Said; Payahoo, Laleh (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objectives. Diabetes mellitus is a serious health-treated problem identified by disorders such as insulin resistance, dyslipidemia, and inflammation. Irisin, a newly discovered myokine/adipokine, is involved in metabolic homeostasis. The present study was carried out to investigate the potential relationship between serum irisin with inflammatory cytokines, oxidative stress biomarkers, glycemic indices, and lipid profiles in obese patients with type 2 diabetes mellitus. Methodology. This analytical cross-sectional study was conducted on 62 participants (n=32 obese participants with diabetes, n=30 participants with normal weight). The participants answered a demographic questionnaire. Serum irisin, glycemic indices, lipid profiles, inflammatory cytokines and oxidative stress biomarkers were measured using standard methods. The difference between groups was assessed by independent-sample t-test or by a non-parametric equivalent. For qualitative variables, the Chi-Square test was used. Pearson rho coefficient was used to determine the potential relationship between irisin and inflammatory cytokines, oxidative stress biomarkers, glycemic indices, and lipid profiles. A p<0.05 was defined as significant. Results. The median (IQR) age of the obese participants with diabetes was 54.0 years (52.2-60.7) and in the normal weight group was 38.0 years (30.0-47.2) (p<0.001). About 78% and 60% of participants in the obese with diabetes and the normal weight groups were females (p>0.05), respectively. Significant differences were observed in serum irisin levels between the two groups, with lower levels (218.74 ng/mL, [144.98-269.26]) noted in the obese with diabetes group compared to the normal weight group (266.68 ng/mL, [200.64-336.57]) with a p=0.024. There was a substantial difference between the two groups regarding IL-6, TNF-α, and hs-CRP (p<0.05). IL-6 had a moderate negative correlation with irisin in obese patients with T2DM (r=-0.478, p=0.006). Conclusion. Irisin concentration was detected to be lower in obese people with diabetes. A negative relationship was detected between irisin and IL-6. Considering emerging evidence about the beneficial functions of irisin in improving metabolic abnormalities, designing future studies with greater sample sizes that will validate these results is needed.